2019
DOI: 10.22201/fca.24488410e.2020.2316
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effect of internal audit on the relationship between corporate governance mechanisms and corporate performance among Saudi Arabia listed companies

Abstract: <p>This study primarily aimed to assess the internal audit function’s ability to detect and self-report fraud. The paper investigated the moderating role of internal audit on the relationship between corporate governance mechanisms and corporate performance (ROA) and the direct effect of corporate governance characteristics and internal audit characteristics on corporate governance of firms listed in the stock market of Saudi Arabia. one hundred and eighty-eight observations obtained from forty-seven Sau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 74 publications
(72 reference statements)
1
25
0
Order By: Relevance
“…For example, a study by Guidara et al ( 2021 ) aimed to assess the relationship between the effectiveness of assurance standards and sustainability by using a sample from 125 countries. Al-Matari and Mgammal ( 2019 ) reported that multi-country studies can provide basic and important insights that enable researchers to understand the subject under investigation from various cultural, social, and political aspects.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a study by Guidara et al ( 2021 ) aimed to assess the relationship between the effectiveness of assurance standards and sustainability by using a sample from 125 countries. Al-Matari and Mgammal ( 2019 ) reported that multi-country studies can provide basic and important insights that enable researchers to understand the subject under investigation from various cultural, social, and political aspects.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of audit committee size, all of their members must be independent and at least three members should be appointed (Securities Commission, 2017). Literature on the size of the RC indicates that there is inconsistent conclusion on the impact of RC size on company's performance; where in some cases the size has a positive effect (Tao and Hutchinson, 2013;Abubakar et al, 2018;Al Matari and Mgammal, 2020) but other studies find the opposite (Kallamu et al, 2013;Battaglia et al, 2014;Elamer and Benyazid, 2018;Kakanda et al, 2018). This raises question whether small or large RCs are effective governance mechanism.…”
Section: 23mentioning
confidence: 99%
“…Companies use governance as one of the mechanisms related to agency theory to ensure that the behavior of executive managers and workers within companies is controlled, in order to achieve the interests of owners and shareholders while avoiding special interests [14]. Furthermore, the government is based on incentive rules, which motivate agents to act in the interests of the entrusting party rather than their own personal interests, as well as the existence of rules to control behavior, which achieve separation between the agent's interests and the interests of the clients, in a manner that achieves the company's basic interest, which is to make a profit, and the interests of the shareholders in this company [15]. Finally, this next part aims to deal with previous studies related to the current study as follows.…”
Section: Literature Review and Methodologymentioning
confidence: 99%